Seismic intervention options for multi-tiered Nepalese Pagodas: The case study of Jaisedewal temple. (May 2021) - Dais, Dimitris; Sarhosis, Vasilis; Smyrou, Eleni; Bal, İhsan Engin
Highlights: Investigation for the restoration and seismic enhancement of Nepalese Pagodas. The exposed foundation significantly affects the seismic response of the temple. Pushover analysis cannot reproduce the dynamic response of the Nepalese temples. Stiffening the connections along the temple enhances the overall seismic behaviour. The benefits of strengthening the expose foundation were found to be insignificant. Abstract: During the 2015 Gorkha earthquake of 7.8 Mw that hit Kathmandu Valley, Nepal, numerous Nepalese Pagodas suffered extensive damage while others collapsed. Risk reduction strategies implemented in the region focused on disassembling historical structures and rebuilding them with modern material without in depth analysis of why they suffer damage and collapse. The aim of this paper is to evaluate the effectiveness of low-cost, low-intervention, reversible repair and strengthening options for the Nepalese Pagodas. As a case study, the Jaisedewal Temple, typical example of the Nepalese architectural style, was investigated. A nonlinear three-dimensional finite element model of the Jaisedewal Temple was developed and the seismic performance of the temple was assessed by undertaking linear, nonlinear static and nonlinear dynamic analyses. Also, different structural intervention options, suggested by local engineers and architects working in the restoration of temples in Nepal, were examined for their efficacy to withstand strong earthquake vibrations. Additionally, the seismic response of the exposed foundation that the Nepalese Pagodas are sitting on was investigated. From the results analysis, it was found that pushover analysis failed to capture the type of failure which highlights the necessity to perform time-history analysis to accurately evaluate the seismic response of the investigated temple. Also, stiffening the connections along the temple was found to enhance the seismic behaviour of the temple, while strengthening the plinth base was concluded to be insignificant. Outputs from this research could contribute towards the strategic planning and conservation of multi-tiered temples across Nepal and reduce their risk to future earthquake damage without seriously affecting their beautiful architectural heritage.